Bilateral vertex extradural hematomas: A case report - Datta, SGS (Indian Journal of Neurotrauma, 2008)
Bilateral vertex extra dural hematomas (EDH) are a rare form of extra dural hematomas with many unique features. We report one such case of bilateral vertex extra dural hematoma. A young house wife had a fall in the bathroom and sustained head injury. She showed clinical features of progressive raised intra cranial pressure. Neuroimaging revealed bilateral vertex EDH. The larger left sided hematoma was evacuated surgically while the smaller right sided hematoma was managed non operatively, with excellent outcome. This case report presents this rare case and briefly reviews the literature. Vertex EDH has a special uniqueness as to their etiopathology, clinical presentation, diagnosis & management principles.
Keywords: Head injury; Vertex EDH